100 easy classics for piano - Manhire, Wilson (Faber Music)
Air (from the water music) -- Ballet music (from Rosamunde) -- Chanson triste -- Dance of the hours -- España -- Fantasie impromptu -- Habanera (from faust) -- Invitation to the waltz -- La golondrina (The swallow) -- March (from casse noisette) -- Nocturne in E flat -- O for the wings of a dove -- Pas des fleurs (intermezzo from Naila) -- Radetzky march -- Serenade -- The skaters' waltz -- Valse (Op 64, No 2) -- Waltz (from faust) -- Zampa.